The Role Of Negotiation In Determining Decisions In International Business Transactions - Nuraini, Berliana Deslita (Universitas Ibn Khaldun Bogor, 2025)
This study explores the critical role of negotiation in international business transactions amid a rapidly evolving and complex global environment. Using a qualitative methodology grounded in literature analysis, it investigates how cultural differences and geopolitical factors affect strategies and outcomes in cross-border business negotiations. The findings reveal that dimensions such as cultural values, communication styles, time orientation, and conflict resolution methods significantly influence negotiation dynamics. Moreover, global economic instability and geopolitical pressures introduce additional complexities that require negotiators to integrate political, regulatory, and economic considerations into their strategies. The study concludes that international negotiation has evolved into a multidimensional mechanism that requires intercultural competence, strategic flexibility, and comprehensive risk analysis. Practical recommendations are presented to aid business actors in managing the challenges of global uncertainty.